Reconceptualizing English Education in a Multilingual Society English in the Philippines (English Language Education, 2018)
This book brings together chapters that describe, investigate, and analyze the place of English in education in multilingual Philippines. Unlike most studies on languages in education, which take a neutral, de-contextualized stance, this volume take a pluricentric view of the English language by positioning it in relation to its varieties, as well as to other languages in the country. Because of the changing realities of English in the Philippines, traditional assumptions about the language as monolithic and unchanging, as well as about how it should be taught and learned, need to be revisited and re-conceptualized.